PENGETAHUAN PETUGAS PERPUSTAKAAN DALAM MENGELOLA PERPUSTAKAAN (Studi SMP Satu Atap Pada SD Negeri 7 Konawe Selatan) - Rama Adrianto Yunus (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2017)
The problem in this research is How Knowledge of Library Officer In Managing Library. The purpose of this study is to determine the extent of knowledge of teachers in managing the library. The research was conducted at the library of State Elementary School 7 Konawe Selatan. In this study, the author uses descriptive research that is to describe the facts and the nature of the relationship between the phenomena investigated. With qualitative method that is to understand the phenomenon of what experienced research subjects by way of describing and collecting data through the library and field with interview and observation techniques with 3 informants as data sources. The results of this study indicate that the knowledge of the librarian of the State Elementary School 7 Konawe Selatan is still very less where the management has not yet applied the classification and cataloging, for the maintenance of library materials is still not effective and the service process to the pemustaka is good enough because it has implemented the service system open acess it can be concluded based on the results of interviews conducted by researchers to officers at the State Elementary School Library 7 Konawe Selatan.  Keywords: Knowledge, Librarian, Management